Evaluation of small ruminant marketing in coastal Kenya - Otieno, L.; Ackello-Ogutu, A.C.; Mullins, C.; Reynolds, L. (Small Ruminant Collaborative Research Support Program, 1993)
The marketing system of small ruminants in coastal Kenya was studied through a case study in Kilifi and Kwale districts. Five channel levels were identified. 1) producers, 2) assemblers, 3) itinerant traders 4) retailers, and 5) consumers. Price discovery was by one-to-one bargaining at all the channel levels. Prices per head were dependent on animal characteristics and market supply conditions including supply from outside the study area. Analysis of marketing margins and cost as well as market integration evaluation indicated that the marketing system was both technical and price efficient.